BIOREDUCTION AND FORMATION OF GOLD NANOPARTICLES BY SOLANUM TORVUM LEAVES EXTRACT - B.S. NAVEEN PRASAD; T.V.N. PADMESH (International Journal of Pharma and Bio Sciences, 2014)
Development of biologically inspired experimental processes for the synthesis of nanoparticles might be important in biomedical applications. Solanum torvum extract when challenged with chloroauric acid leads to formation of gold nanoparticles. The formations of gold nanoparticles were studied by UV-vis spectra and their size of gold nanoparticles in the colloidal solutions was investigated by HRTEM, the average size of gold nanoparticles nanoparticles was found to be 8.4 nm. The rapid reduction of AuCl4- ions highlights the possibility of green pathways to produce technologically important nanomaterials